Percepción de los pobladores de la ciudad de San Lorenzo sobre problemas ambientales, provincia del Datem del Marañón. Región Loreto. 2020 - Nuñez Chimpa, Jhamlith Yampan (2022)
The study on the perception of the inhabitants of the city of San Lorenzo on environmental problems, province of Datem del Marañón, Loreto region. 2020, aims to evaluate the perception or appreciation of the inhabitants of this city on environmental problems. It is a study of the descriptive type and simple design. A sample of 298 people over 18 years of age who live in the city was considered. Work was based on a survey, which was developed using descriptive statistics. It is concluded: the perspectives of the environment were evaluated in people, where they say that the environment is natural resources (28.3%), (25%) states that the environment is pollution and 24.3% flora and fauna. Regarding environmental attitudes, such as opinions on how to safeguard the environment and conserve resources, the results tell us that these people do not comply with environmental legislation because they do not know it (83.89%), and they consider that the mismanagement of solid waste ( 36.9%) and the contamination of surface waters (24.2), the most critical problems in the city. They prefer to conserve resources in the present for the use of other generations in the future. Regarding environmental responsibility, they believe that they feel guilty for the environmental situation of the city (50.34%), where they consider that municipal work is only regular (80.54%), and they argue that they do not receive training on environmental issues (85.9%). The environmental training of people is low, 32.52% report not receiving any information on the subject of study, but they consider that learning or knowledge about these issues would raise people's environmental awareness (60.40%) and suggest implementing education programs environmental (29.2%), creation of community groups to train people about the environment (23.32%) and fines for offenders who pollute the environment (23.32%). The work allows us to say that the perception that people recognize environmental problems and their identification.